2019
DOI: 10.1061/jswbay.0000880
|View full text |Cite
|
Sign up to set email alerts
|

Green Infrastructure Implementation in Urban Parks for Stormwater Management

Abstract: A newly constructed rain garden in Shoelace Park in Bronx, New York, USA, was monitored between October 2014 and July 2015 as a pilot study aimed at testing the effectiveness of using urban park space to manage adjacent street runoff. Street inlet capture efficiency and rain garden retention were assessed through inflow and outflow monitoring and quantification. During the monitoring campaign consisting of 26 storms, the rain garden retained an average of 78% of all inflows, with full retention for storms unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The authors suggest this demonstrates the potential for storage and reuse of bioretention outflows as a secondary nonpotable water source in dense urban areas. A rain garden in a high-density area in New York that intercepted street runoff retained 78% of all inflow volume, with 100% of retention of storm flow volumes associated with 26 rainfall events less than 10 mm (Feldman, Foti, & Montalto, 2019). The authors make the case that by retrofitting just 4% of the green space with green infrastructure, a 10% lowering of storm flow might be achieved.…”
Section: Field Laboratory and Modeling Performance Studies: Field Smentioning
confidence: 99%
“…The authors suggest this demonstrates the potential for storage and reuse of bioretention outflows as a secondary nonpotable water source in dense urban areas. A rain garden in a high-density area in New York that intercepted street runoff retained 78% of all inflow volume, with 100% of retention of storm flow volumes associated with 26 rainfall events less than 10 mm (Feldman, Foti, & Montalto, 2019). The authors make the case that by retrofitting just 4% of the green space with green infrastructure, a 10% lowering of storm flow might be achieved.…”
Section: Field Laboratory and Modeling Performance Studies: Field Smentioning
confidence: 99%
“…Green open spaces provide multiple services to human beings, including ecological, social, economic, and health benefits. Previous studies have demonstrated that green open space can provide a wide range of services such as the alleviation of urban heat [8,9], mitigating stormwater [10,11], conserving soil [12], enhancing biodiversity [13,14] and filtering pollutants [15,16]. Wu et al [17] found that proximity to parks significantly increased real estate prices and led to economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…Use of a relatively small amount of greenspace for siting level spreaders and other GSI may have an outsized benefit for stormwater management in a city. Feldman, Foti, and Montalto (2019) , 2019). This may facilitate permitting of level spreader construction.…”
Section: Site Selectionmentioning
confidence: 99%